Comparative physicochemical properties and anti-inflammatory activity of natural and artificial musk for quality evaluation - Shuya Li; Bumarya Rahimjan; Hang Jie; Yiwu Wang; Yuan Shen; Jialing Yu; Lin Yang; Dan He (Scientific Reports)
Abstract In this study, we conducted a comprehensive comparative analysis of the physicochemical properties of natural musk (NM) and artificial musk (AM), focusing on their ultrastructure, volatile constituents, alcohol-soluble compounds, amino acid composition, inorganic element content and anti-inflammatory activity. Advanced analytical techniques such as scanning electron microscopy (SEM), gas chromatography-mass spectrometry (GC-MS), liquid chromatography-mass spectrometry (LC-MS), amino acid auto analyzer (AAA), and inductively coupled plasma-mass spectrometry (ICP-MS) were utilized to evaluate the differences in their physicochemical properties. The results of the study showed that SEM could distinguish NM and AM based on their surface morphology. GC-MS and LC-MS results identified 15 volatile compounds and 25 alcohol-soluble compounds in NM, whereas AM contained 8 volatile compounds and 22 alcohol-soluble compounds, indicating a more complex chemical constituent in NM. Amino acid analysis revealed that AM contained 787.1 mg/g total amino acids, significantly higher than the 156.4 mg/g found in NM. The determination of inorganic elements highlighted the differences in elemental content and identified the characteristic elements in both musks Specifically, K, Al, Ni, As, and Hg were characteristic of NM, while Na, Fe, Al, Co, Cu, Ag, Ba, and Pb were characteristic of AM. In addition, the results of in vitro anti-inflammatory tests showed the starting concentration of NM (0.025 mg/mL) and AM (0.05 mg/mL), indicating that NM and AM cannot be used interchangeably in clinical applications. This study provides a valuable reference for differentiating between NM and AM, providing insights into their utilization and development.